Awareness and involvement of fathers in care of their under five children in Jorpati, Kathmandu: A cross Sectional Study (Journal of Kathmandu Medical College, 2018)
Background: Children are not just mini human creatures, they are different entities and have unique need for care, nourishment, play, interaction and harmonious environment. Both parents are equally responsible for providing such environment for optimum growth and development of children. Involvement of fathers in care not only promotes their physical development but also fosters social, cognitive, language and motor development.Objectives: To assess the awareness and involvement of fathers in care of their under five children.Methodology: A community based cross sectional study was conducted at Anandanagar tole Gokarneshwar Municipality-8 Jorpati among 128 fathers with children under five years of age. Information was collected through face to face interview using structured questionnaire consisting of statement regarding awareness and involvement in care of their under five years children. Data analysis was done by using statistical package for social science version 16.Results: Majority (60.1%) of the fathers had average level of awareness about child care. Regarding involvement, 44.5 % of the fathers had poor involvement followed by average involvement i.e. 41.4% in physical care. Around two third (68.9%) of the fathers showed average involvement in psychological and intellectual developmental activities of their children.Conclusion: This study shows that though most of the fathers had average awareness regarding childcare, their involvement in the same was less especially in physical care activities.